Oral Cytotoxic Chemotherapy Safe Use and Safe Handle Among Cancer Patients in Radiation and Isotopes Center, Sudan - Mohamed, Alaa Abdelaziz; Mousnad, Mohamed Awad (International Journal of Innovative Research in Medical Science, 2019)
Background: Increasing use of oral cytotoxic chemotherapy among cancer patient in Sudan, rising important concern about safety practicing and using of these drugs. This study aimed to assess and demonstrate patient awareness regarding their oral cytotoxic drugs regimen in Radiation and Isotopes Center at Khartoum (RICK), as it considered one of the essential hospital cancer treatments in Sudan. Method: Across-sectional study was carried out at (RICK) hospital outpatient pharmacies. Data were collected by interviewing 100 patients and answering question about their drug regimen, side effects & management, handling & storage and drug/food/herb interactions. Result: The study showed that 46% of participants have missing knowledge about their drug using and taking. Complaints reported by patients, when using their drugs, vary. Myelosuppression is the most common (40.2%). In side effect management, the study showed that 26% of the patients are referred to the community pharmacy and 67% are using medication without a prescription. Regarding the awareness of using herbal treatments, 42% of patients are using or have used herbs with their drugs. 69% of patients using herbs said that they do not inform the caregiver. For the proper drug handling and storage in the home setting, 59.6% of patients said they did not receive instructions about handling and storage. The degree of patient knowledge about the proper handling and storage are variable. Finally, patient's knowledge about their drug regimen was significantly associated with drug education, an age of 13-45 years and regularity of clinic visits (p =0.018). Conclusion: The study concluded that awareness of patients is very low regarding the toxicity of these drugs and education of patients for oral cytotoxic chemotherapy vary substantially. The development of therapeutic educational programs is essential to ensure safe practice when using oral cytotoxic drugs.